Non-durational indices in Italian geminate consonants - Payne, E (Cambridge University Press, 2006)
This paper presents the results of an electropalatographic investigation into non-durational properties of Italian consonant gemination. The evidence suggests a more palatalised tongue configuration during the production of geminate coronal sonorants and stops than in their non-geminate counterparts. Evidence is also found of differences in the active articulator, with a laminal articulation more characteristic of geminates, and an apical articulation of non-geminates. It is proposed that Italian gemination be thought of more broadly as fortition, and the implications of this are discussed.